A new species of the genus Parachauliodes (Megaloptera: Corydalidae: Chauliodinae) from Northern Kyushu, Japan - Shimonoya, Mitsuru (Zootaxa, 2019)
A new species of the genus Parachauliodes van der Weele, 1909, P. rastellus sp. nov., is described from northern Kyushu, Japan. This new species is most similar to P. japonicus (McLachlan) and differs by the form of the male antenna and genitalia. Parachauliodes is primarily characterized by the “bilobed” ectoproct of male genitalia and by the serrate antenna of both sexes. In the new species, the male ectoproct is bilobed, but sexual dimorphism in the antennae is present. The male antenna of the new species is pectinate with short branches and the female antenna is serrate. Accordingly, including the new species P. rastellus, the antennae of Parachauliodes can either be serrate or pectinate with short branches in the male, serrate in the female. The types of “Parachauliodes” buchi Navás are illustrated. A brief description of copulation, oviposition, eggs and hatching for the new species is also given.